Peripancreatic schwannoma: A case report. (June 2021) - Moussa, Sumer; Cruz, Stephanie; Ingram, Mark; Zuberi, Jamshed
Abstract: Introduction: Schwannomas are a benign tumor of peripheral nerve sheath origin. Although most commonly arising in the extremities, head, and neck there have been rare cases of schwannomas presenting within or adjacent to the pancreas reported in the literature. Presentation of case: We present an asymptomatic and otherwise healthy 57-year-old male with an incidental peripancreatic mass measuring 3.5 × 3.7 cm found on abdominal computed tomography (CT). The patient underwent complete enucleation of the mass at our hospital. Pathological analysis of the excised specimen showed spindle shaped cells. Immunohistochemical staining was positive for S100 protein expression, confirming the definitive diagnosis of peripancreatic schwannoma. The patient's postoperative course was uneventful. Discussion: Schwannoma is a commonly benign, encapsulated, and slowly growing tumor arising from myelin producing cells of peripheral nerves. A schwannoma presenting within or adjacent to solid abdominal viscera, such as the pancreas, may be challenging to diagnose preoperatively as it may mimic other lesions. Radiological appearance of schwannoma may be nonspecific and definitive diagnosis is reliant upon pathological analysis. The use of endoscopic ultrasound (EUS) with fine needle aspiration (FNA) may assist the clinician in preoperative diagnosis, however these interventions are not widely available. Accurate preoperative diagnosis of a peripancreatic schwannoma is of high importance as it may preclude unnecessary pancreatectomy or radical resection. Conclusion: Although rare, schwannoma should be part of the differential diagnosis of a cystic or solid appearing mass within or surrounding the pancreas. Total resection carries an excellent prognosis with little to no documented recurrence. Highlights: Peripancreatic schwannoma is rare, but should be considered in the differential diagnosis of an incidentally found mass Histopathological features of schwannoma Radiological features of schwannoma Enucleation of peripancreatic schwannoma carries excellent prognosis